The influence of job rotation on career development among employees in Lembaga Zakat Negeri Kedah (LZNK) / Muhammad Mifzal Mat - Mat, Muhammad Mifzal (2019)
This study investigated the relationship between job rotation practices and employee career development prospects among employees of Lembaga Zakat Negeri Kedah. It examines the extent to which job rotation practices are significant to career development that consist of administrative knowledge, technical knowledge and business knowledge. A model of job rotation developed by Campion, Cherakin and Stevens (1994) was used as the premise to test the linear relationship between job rotation and employee career development in the workplace. This is done by analyzing survey-based data sets particularly obtained from samples of 113 Lembaga Zakat Negeri Kedah employees. The Pearson Correlation was used to measure the association between the variables and to test the research hypotheses. The results of the study found that there were significant correlation between job rotation practices and career development. Multiple regression result indicate that all dimensions of job rotation except administrative knowledge influence career development.